Photodynamic therapy for the treatment of buccal candidiasis in rats - Junqueira, Juliana Campos [UNESP]; Martins, Joyce da Silva [UNESP]; Faria, Raquel Lourdes [UNESP]; Dias Colombo, Carlos Eduardo [UNESP]; Cardoso Jorge, Antonio Olavo [UNESP] (Springer London Ltd, 2009)
The study objective was to evaluate the effects of photodynamic therapy on buccal candidiasis in rats. After experimental candidiasis had been induced on the tongue dorsum, 72 rats were distributed into four groups according to treatment: treated with laser and methylene blue photosensitizer (L+P+); treated only with laser (L+P-); treated only with photosensitizer (L--P+); not treated with laser or photosensitizer (L-P-). The rats were killed immediately, 1 day, or 5 days after treatment, for microscopic analysis of the tongue dorsum. Observation verified that the photodynamic therapy group (L+P+) exhibited fewer epithelial alterations and a lower chronic inflammatory response than the L-P- group. The group L+P- presented more intense epithelial alterations and chronic inflammatory response than the remaining groups. The L-P+ group showed tissue lesions similar to those of the L-P- group. In conclusion, rats treated with photodynamic therapy developed more discrete candidiasis lesions than did the remaining groups.
Keywords: Photodynamic therapy; Methylene blue; Candida albicans